Acute and Chronic Effects of Muscle Strength Training on Physical Fitness in Boxers: A Scoping Review - Herrera-Valenzuela, T; Cid-Calfucura, I (Multidisciplinary Digital Publishing Institute (MDPI), 2024)
Featured Application: It is possible to improve punches’ impact force both chronically and acutely. Before fights or sparring sessions, maximal isometric exercises can be integrated with punching techniques (e.g., three repetitions of 3 s), resistance band exercises with punching techniques (e.g., two sets of 5 reps), medicine ball throws with 10% of 5RM bench press (e.g., three sets of 8 reps), SJ with 30% of 1RM (e.g., four sets of 8 reps) and traditional exercises such as bench press and back squat with 80% of 1RM (e.g., three sets of 5 reps) with an improvement window in punches’ impact force between 6 and 15 min after the exercises. The aim of this scoping review was to compile the current evidence and provide a summary of the acute and chronic effects of muscle strength training on the physical fitness of amateur boxers and provide recommendations to optimize their physical performance. This scoping review was developed using guidance from the Joanna Briggs Institute and PRISMA-ScR. The search was conducted in the Scopus, PubMed and Web of Science databases between December 2023 and June 2024. In total, 50 full-text articles were assessed to determine eligibility, while 15 studies met the inclusion criteria and were subjected to detailed analysis and assessment of their methodological quality. Our findings indicate that muscular strength training interventions can improve punching performance in amateur boxers acutely and chronically, in addition to improving their physical fitness and generating increases in the capacity to generate maximum force and improvements in RFD and the power production of the upper and lower limbs of boxers. However, this scoping review only included one study in female boxers, so we recommend that future studies contain muscular strength training interventions in females to analyze their adaptations in punching force and physical fitness. © 2024 by the authors.